A jumping spider that lays eggs like an insect. Issue 4 (2nd October 2017) - Hawes, Timothy C.
Abstract: The South East Asian salticid, Asemonea tenuipes, lay its eggs like an insect: as individuated capsules in geometrically precise rows. The occurrence of this behaviour is described in a population from Thailand that lays eggs on the underside of mango tree ( Mangifera indica ) leaves. The rows were vertically arranged at a 90° angle that was parallel to, and varied in relation to the angle of the central leaf rib, indicating that the rib serves as the primary visual cue for orienting the row. Analysis of within-egg row symmetry found evidence that micro-topography – in particular, vertical 'stepping' produced by leaf sub-ribs – of the leaf surface plane was responsible for 97% of variability in the relative symmetry of egg placement. Three strategies were identified: (1) crossing the sub-rib and producing localized asymmetry in the egg row; (2) introducing a gap at the sub-rib to maintain symmetry; and (3) 'compressing' the egg row into the gap between sub-ribs. The incidence of asymmetry showed a highly significant linear relationship with egg load. It is hypothesized that the use of rows probably represents a solution to the problem of how to surveil temporally staggered clutches of eggs and newly hatched spiderlings simultaneously.